Adenovirus 36 infection: a role in dietary intake and response to inpatient weight management in obese girls - Zamrazilová, H; Aldhoon-Hainerová, I; Atkinson, R L; Dušátková, L; Sedláčková, B; Lee, Z P; Kunešová, M; Hill, M; Hainer, V (International journal of obesity (2005), 2015)
Human adenovirus 36 (Adv36) increases adiposity and is more prevalent in overweight and obese children. Dietary intake in animal models is comparable regardless of Adv36 status. The effects of Adv36 on obesity treatment outcomes have not been clarified. The aim of this study is to investigate the pre-treatment dietary intake and the response to a 4-week inpatient weight management in 184 obese adolescent girls aged 13.0-17.9 years with respect to the presence of Adv36 antibodies. Evaluation of 3-day dietary records did not show any difference in daily intake of energy and essential nutrients between Adv36 antibody positive and negative girls. After the intervention Adv36 positive girls presented with significantly greater decrease of waist circumference (P=0.020), z-score of waist circumference (P=0.024), waist-to-hip ratio (P=0.007) and weight-to-height ratio (P=0.019) compared with Adv36 negative girls. On the contrary, the sum of four skinfolds decreased significantly more in Adv36 negative than in Adv36 positive individuals (P=0.013). Neither body fat percentage nor metabolic and hormonal parameters showed any significant relevance to Adv36 status in response to weight loss intervention. In conclusion, energy restriction in Adv36 antibody positive girls was associated with greater decrease of abdominal obesity and preservation of subcutaneous fat tissue than in those antibody negative.
Keywords: Inpatients; Adenovirus Infections, Human; Diet Records; biologické markery; protilátky virové; Risk Factors; poměr pasu a boků; Biomarkers; Adolescent; Česká republika; dietní záznamy; obezita dětí a dospívajících; Disease Susceptibility; mladiství; Czech Republic; hospitalizovaní pacienti; lidé; ženské pohlaví; Humans; adenovirové infekce lidí; rizikové faktory; Antibodies, Viral; Adenoviruses, Human; Pediatric Obesity; náchylnost k nemoci; Female; Waist-Hip Ratio; lidské adenoviry